The Utilization of Instructional Media by the Vocational High Schools Teacher - Dwihartanti, Muslikhah; Sutirman, Sutirman; Yuliansah, Yuliansah (Dinamika Pendidikan, 2021)
This study examines the use and development of instructional media by the teachers of Office Administration Vocational School (OAVS) in the Special Region of Yogyakarta (DIY). The population of this survey research is all teachers of OAVS in DIY. This research employed the purposive sampling technique and considered only the teachers who had been teaching productive subjects for at least five years. The descriptive analysis technique was used to conduct the data analysis. The result shows all the teachers of OAVS in DIY have utilized learning media in teaching and learning activities. The most widely used type of instructional media is the PowerPoint. The technical constraints experienced in utilizing learning media are related to the preparation of using learning media. While the non-technical are related to the availability of facilities and infrastructure. Teachers of OAVS in DIY who have developed learning media are still at a low level. Technical things experienced by teachers in developing learning media are constrained in the process of planning the development of learning media and should look for media experts who will validate. The non-technical constraints faced by teachers in media development are issues about facilities and low teacher motivation.